(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The study of the interaction of intercalators ethidium bromide (EtBr), methylene blue (MB) and groove binding compound Hoechst 33258 (H33258) with single-stranded synthetic polyribonucleotides poly(rA) and poly(rU) has been carried out by the method of UV-melting, at ionic strengths of the solution 0.04 M and 0.1 M. Stirring of poly(rA) and poly(rU) by equal-molar concentrations was shown to result in hybridization with formation of double-stranded (ds-) structure poly(rA)-poly(rU). It was revealed that EtBr, with higher degree in comparison with MB, stimulates hybridization and stabilizes the formed ds-structure poly(rA)-poly(rU). It was also found out that the hybridization process and affinity of EtBr and MB depend on the ionic strength of the solution and these processes occur much more effectively at the ionic strength 0.04 M. On the other hand, it was shown that the groove binding ligand H33258 practically does not affect the stabilization of the formed ds-structure poly(rA)-poly(rU).